Management Information System Innovation in Developing the Quality of Educational Services at the Amanatullah Islamic Boarding School in Banyuwangi - Istikomah Istikomah; Mufidah Cholil; Khotimatus Solikhah (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This research, entitled "Innovation of Management Information Systems in Developing the Quality of Educational Services at the Amanatullah Islamic Boarding School in Banyuwangi," is motivated by a unique phenomenon at the institution. Amidst the current of global modernization, the Amanatullah Islamic Boarding School in Banyuwangi remains consistent in maintaining the identity and culture of a salafiyah Islamic boarding school that is steeped in traditional values. However, on the other hand, this Islamic boarding school demonstrates openness to technological advancements through the implementation of a digital application-based Management Information System (MIS). This study aims to discover, describe, and analyze in depth the innovations in product aspects and innovations in human resources aspects in the management information system to improve the quality of educational services at the institution. The research method used is a qualitative approach with a case study type. The researcher acts as the main instrument in data collection conducted through participatory observation techniques, in-depth interviews with caretakers, administrators, and system operators, as well as documentation studies related to academic and managerial data. The validity of the data is tested through triangulation of sources and techniques to ensure the objectivity of the findings in the field. The research results show that innovation in the product aspect is realized through the development of a standalone digital application that integrates student data, financial administration, and academic progress reports in real time. This innovation provides easy access for student guardians and accelerates internal bureaucratic processes. In the human resources aspect, innovation is carried out through a continuous technology training program and restructuring of operational tasks that encourage Islamic boarding school staff to adapt to digital systems without abandoning Islamic boarding school ethics. Meanwhile, in the facilities and infrastructure aspect, the provision of network infrastructure and hardware is the main support for the sustainability of the SIM. Overall, the integration of salafiyah values ​​​​and modern management through this SIM innovation has proven to be able to increase accountability, transparency, and the quality of educational services, which ultimately supports the achievement of the vision and mission of the Amanatullah Islamic Boarding School in the digital era.